2019
DOI: 10.1080/15685551.2019.1687083
|View full text |Cite
|
Sign up to set email alerts
|

Role of sequence of feeding on the properties of polyurethane nanocomposite containing halloysite nanotubes

Abstract: Polyurethane/Halloysite Nantubes nanocomposites containing 1 wt.% nanoparticles were prepared using in situ polymerization method with different mixing sequences. Various experiments have been performed in order to evaluate the effect of nanoparticle dispersion and the different orders of mixing of the samples on the mechanical properties and morphology of nanocomposites. The results obtained from the ATR-FTIR test demonstrated that the presence of nanoparticles led to an increase in phase separation, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The degree of phase separation (DPS) was determined using the equation: DPS = R/(R + 1). According to the literature, with R increasing, the degree of phase separation in polyurethanes increase [ 40 ]. It was observed that the degree of phase separation of obtained bio-TPU depends on the content of the hard segment, and the same, on the amount of bio-based diisocyanate in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of phase separation (DPS) was determined using the equation: DPS = R/(R + 1). According to the literature, with R increasing, the degree of phase separation in polyurethanes increase [ 40 ]. It was observed that the degree of phase separation of obtained bio-TPU depends on the content of the hard segment, and the same, on the amount of bio-based diisocyanate in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…These results are shown in Figure 2 and summarised in Table 2 . The addition of up to 7.5 wt.% unmodified LigW particles to bioPUR foam shifted the glass transition temperature to higher temperatures due to the constraints of polymer chains [ 34 ]. The maximum increase in T g can be observed for 5 wt.% LigW-modified bioPUR foam composites ( Figure 2 a), while further addition of LigW particles reduced T g to 140 °C, which is 5 °C lower compared to the control bioPUR foam due to the easier movement of the soft segments in the 10 wt.% LigW.…”
Section: Resultsmentioning
confidence: 99%
“…The nanocomposite did not show any aggregation of graphene suggesting homogenous dispersion within the matrix. [ 38–40 ] However, TPU‐2.0 showed some bright spots on the surface, which could be graphene nanoplatelets either dispersed or aggregated nanoplatelets. From the EDS analysis, upon increasing the graphene loading the carbon content and oxygen content increased.…”
Section: Resultsmentioning
confidence: 99%